Produk E-Money Bank Syariah dalam Perspektif Kajian Islam - Dian Lestari Styaningrum; Purnama Putra (LPPM Universitas Islam 45, 2023)
This study aims to determine the suitability of BSM E-Money products according to the DSN MUI Fatwa on one of the products at Bank Syariah Mandiri. This study used a qualitative descriptive method with data collection carri ed out through observation, interviews and documentation of two sources of informants, namely the Central Bank Syariah Mandiri Office and the DSN-MUI Institute Office. Data analysis techniques were carried out in three steps, namely: data reduction, data presentation, and drawing conclusions. The results of this study indicate that according to the DSN-MUI Fatwa, a product that has been legalized and marketed states that the product is in accordance with the DSN-MUI Fatwa No. 116 because if the product is not in accordance with the existing Fatwa or violates the provisions, the Bank Indonesia Authority or OJK has the authority to reprimand or stop the product. According to Bank Syariah Mandiri, so far BSM E-Money products are still operating in accordance with existing regulations, it can be concluded that Products in Electronic Money transactions at Bank Syariah Mandiri have complied with DSN-MUI Fatwa No. 116, approved by the Sharia Supervisory Board (DPS) and obtained a permit from Bank Indonesia or the Financial Services Authority (OJK). The product complies with sharia principles and is declared in accordance with the DSN-MUI Fatwa, only that there are sharia problems.